Lyophilized hybrid nanostructured lipid carriers to enhance the cellular uptake of verapamil: statistical optimization and in vitro evaluation - Khan, Arshad Ali; Abdulbaqi, Ibrahim M.; Assi, Reem Abou; Vikneswaran, Murugaiyah; Yusrida, Darwis (Springer Open, 2018)
Verapamil is a calcium channel blocker and highly effective in the treatment of hypertension, angina pectoris, and other diseases. However, the drug has a low bioavailability of 20 to 35% due to the first pass effect. The main objective of this study was to develop hybrid verapamil-dextran nanostructured lipid carriers (HVD-NLCs) in an attempt to increase verapamil cellular uptake. The formulations were successfully prepared by a high-shear homogenization method and statistically optimized using 24 full factorial design. The HVD-NLCs formulations were freeze-dried using trehalose as a cryoprotectant. The results showed that the optimized formula (VER-9) possessed a particle size (PS), polydispersity index (PDI), and the percentage of entrapment efficiency (%EE) of 192.29 ± 2.98, 0.553 ± 0.075, and 93.26 ± 2.66%, respectively. The incorporation of dextran sulfate in the formulation had prolonged the release of verapamil (~ 85% in 48 h) in the simulated gastric fluid (pH 1.2) and simulated intestinal fluid (pH 6.8). The differential scanning calorimetry analysis showed no chemical interaction between verapamil and the excipients in the formulation. While wide-angle X-ray scattering studies demonstrated the drug in the amorphous form after the incorporation in the NLCs. The transmission electron microscopy and scanning electron microscopy images revealed that the nanoparticles had spherical shape. The cellular uptake study using Caco-2 cell line showed a higher verapamil uptake from HVD-NLCs as compared to verapamil solution and verapamil-dextran complex. The optimized formulation (VER-9) stored in the refrigerated condition (5 °C ± 3 °C) was stable for 6 months. In conclusion, the HVD-NLCs were potential carriers for verapamil as they significantly enhanced the cellular uptake of the drug.